Propagation of Meizotropis buteiformis Voigt - Dhabe, Kavita N. Gaisamudre*; Arvind S. (Journal of Ecobiotechnology, 2011)
The seeds of Meizotropis buteiformis were treated with different scarification treatments viz. - Mechanical treatment, acid treatment, hot water treatment, presoaking and treatment of alkali (NaOH and KOH), thiourea and Indole Acetic Acid (IAA). The stem cuttings were also treated with Indole Acetic Acid (IAA), Indole Butyric Acid (IBA) and Gibberellic Acid (GA). It was observed that the highest percentage of seed germination was recorded in presoaking treatment for 6 hrs, hot water treatment (50Ã‹Å¡C for 15 mins) followed by Conc. H2SO4 (4 min), IAA for 10 mins and thiourea for 10 minutes. The stem cuttings showed highest percentage of sprouting in the treatment of Indole Acetic Acid (IAA) at 200 ppm for four hours.